2009
DOI: 10.1517/17425240903156374
|View full text |Cite
|
Sign up to set email alerts
|

Formulating protein therapeutics into particulate forms

Abstract: This review is aimed at providing critical comments on selected approaches to formulating protein drugs into particulate forms feasible as practical pharmaceutical dosage forms. From a practical point of view, the need to formulate protein therapeutics into particulate forms includes inhalation and sustained-release delivery proteins, stabilizing and incorporating proteins into tissue engineering scaffolds and medical devices, as well as protecting and targeting protein therapeutics in an in vivo environment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…The protein-protective mechanisms occurred because the dextran nanoparticles could provide a glassy state, and the glassy matrix could decrease the encapsulated IFNα-2b mobility and was more resistant to stresses of temperature and moisture. 19,37,41,42 In vivo efficacy study…”
Section: Stability Of Ifnα-2b From Nanoparticlesmentioning
confidence: 99%
See 4 more Smart Citations
“…The protein-protective mechanisms occurred because the dextran nanoparticles could provide a glassy state, and the glassy matrix could decrease the encapsulated IFNα-2b mobility and was more resistant to stresses of temperature and moisture. 19,37,41,42 In vivo efficacy study…”
Section: Stability Of Ifnα-2b From Nanoparticlesmentioning
confidence: 99%
“…These results confirmed that the dextran nanoparticles could also preserve protein activity in vivo. 19,37 This was because the controlled method (W/O/W) produced a larger amount of oil-water interfaces at which IFNα-2b easily aggregated and lost antiviral activity. 19,37,41,42 Samples A, B, C, and D were the same as in Figures 1A-C and 2D.…”
Section: Stability Of Ifnα-2b From Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations